2020
DOI: 10.1149/1945-7111/abb34e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Frictional Interactions on Conductivity, Diffusion, and Transference Number in Ether- and Perfluoroether-Based Electrolytes

Abstract: There is growing interest in fluorinated electrolytes due to their high-voltage stability. We use full electrochemical characterization based on concentrated solution theory to investigate the underpinnings of conductivity and transference number in tetraglyme/ LiTFSI mixtures (H4) and a fluorinated analog, C8-DMC, mixed with LiFSI (F4). Conductivity is significantly lower in F4 than in H4, and F4 exhibits negative cation transference numbers, while that of H4 is positive at most salt concentrations. By relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 65 publications
6
29
1
Order By: Relevance
“…Grundy et al reported the same trend with LiTFSI in G4. 41 The absolute values appeared to agree with Grundy’s findings, although their chosen salt was LiTFSI, so would expect to have a slightly lower D a p p . Compared to other lithium-ion electrolytes, D a p p was quite low, with 1 M PC and EMC-based electrolytes exhibiting values 2–6 times higher.…”
Section: Resultssupporting
confidence: 72%
“…Grundy et al reported the same trend with LiTFSI in G4. 41 The absolute values appeared to agree with Grundy’s findings, although their chosen salt was LiTFSI, so would expect to have a slightly lower D a p p . Compared to other lithium-ion electrolytes, D a p p was quite low, with 1 M PC and EMC-based electrolytes exhibiting values 2–6 times higher.…”
Section: Resultssupporting
confidence: 72%
“…Grundy et al reported the same trend with LiTFSI in G4. [38] The absolute values appeared to agree with Grundy's findings, although their chosen salt was LiTFSI, so would expect to have a slightly lower D app . Compared to other lithium-ion electrolytes, D app was quite low, with 1M PC and EMC-based electrolytes exhibiting values 2-6 times higher.…”
Section: Diffusion Coefficientsupporting
confidence: 71%
“…x-2 field is applied across an electrolyte of uniform concentration [14][15][16][17]. ) measured by 7 Li, 1 H, and 19 F electrophoretic NMR (eNMR) at 30°C: cation (blue), solvent (black) and anion (red). Velocities are in the lab frame of reference.…”
mentioning
confidence: 99%
“…, 𝑣 ' and 𝑣 " are the averaged species velocities of the cation, anion, and solvent, respectively, 𝐹 is the Faraday constant, c is salt concentration and E is the applied electric field [18]. The ionic conductivity and transference number at dilute concentrations can be determined using the Nernst-Einstein equation [19]. For concentrated electrolytes, more rigorous frameworks that capture the ion-ion and the ion-solvent correlations are required [20][21][22][23][24][25], commonly with the aid of computer simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation